2022
DOI: 10.3390/ma15124265
|View full text |Cite
|
Sign up to set email alerts
|

Method for the Evaluation of the Homogeneity of Asphalt Mixtures by 2-Dimensional Image Analysis

Abstract: In order to evaluate the homogeneity of asphalt mixture quantitatively, the distribution characteristic of internal phases of asphalt mixture were identified based on digital image processing technique and stereology theory, and the homogeneity coefficient (i.e., K) was proposed. At the same time, the trend of variation and reliability of homogeneity of asphalt mixture were analyzed by changing the nominal maximum aggregate size, aggregate gradation and asphalt content. The results suggest that the homogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Based on the index of the vertical heterogeneity coefficient, the variation in the construction quality homogeneity in different regions of asphalt pavement can be reflected. Some studies also confirmed that the quantity distribution and location distribution of aggregate particles could effectively characterize the homogeneity of asphalt mixtures [ 33 , 34 ].…”
Section: Evaluation Index Of Component Homogeneity For Asphalt Pavementmentioning
confidence: 91%
“…Based on the index of the vertical heterogeneity coefficient, the variation in the construction quality homogeneity in different regions of asphalt pavement can be reflected. Some studies also confirmed that the quantity distribution and location distribution of aggregate particles could effectively characterize the homogeneity of asphalt mixtures [ 33 , 34 ].…”
Section: Evaluation Index Of Component Homogeneity For Asphalt Pavementmentioning
confidence: 91%
“…Digital image processing uses a series of algorithms to process and analyze digital images with computers so that the images can meet the needs of human vision, other equipment, data extraction, etc. [ 23 ]. In this section, MATLAB software is used to process images, including image enhancement, image filtering, image segmentation, and feature information acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…By generating digital samples from optically scanned surface images of laboratory-prepared asphalt specimens, Xu G et al [10] captured the microstructure of stone-based materials. Through image processing techniques, Sun P et al [11] extracted valuable information regarding the distribution and size of pores within AC mixtures, as Appl. Sci.…”
Section: Ac Microstructure Analysis Using Digital Cameramentioning
confidence: 99%
“…By generating digital samples from optically scanned surface images of laboratory-prepared asphalt specimens, Xu G et al [10] captured the microstructure of stone-based materials. Through image processing techniques, Sun P et al [11] extracted valuable information regarding the distribution and size of pores within AC mixtures, as well as their connectivity. Moreover, the use of fractal analysis techniques can provide insight into the complexity and heterogeneity of crack patterns within AC mixtures [12].…”
Section: Ac Microstructure Analysis Using Digital Cameramentioning
confidence: 99%